2020
DOI: 10.1177/1052684620951722
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Teacher Education Is Nation Building: Reflections of Capacity Building and Capacity Strengthening in Idaho

Abstract: This article discusses the efforts of the Indigenous Knowledge for Effective Education Program (IKEEP), at the University of Idaho, a predominately white institution (PWI) of higher education, and its struggle to create space in higher education for intentional support of Indigenous self-determination, sovereignty, and Tribal nation building through the preparation of Indigenous teachers. In doing so, we examine the contentious and local work of reimagining education, from the bottom up and top down, to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Of the 24 studies included in this review, two studies, Anthony-Stevens et al [34] and Miller and Roehrig [35], reported hybrid programs that occurred in both formal school contexts (i.e., in-school activities) and out-of-school informal settings (i.e., field trip). Both these programs had Indigenous knowledge keepers participating in the implementation as mentors guiding students' field trips.…”
Section: Programs Involving Both Formal and Informal Contextsmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the 24 studies included in this review, two studies, Anthony-Stevens et al [34] and Miller and Roehrig [35], reported hybrid programs that occurred in both formal school contexts (i.e., in-school activities) and out-of-school informal settings (i.e., field trip). Both these programs had Indigenous knowledge keepers participating in the implementation as mentors guiding students' field trips.…”
Section: Programs Involving Both Formal and Informal Contextsmentioning
confidence: 99%
“…In one program, students experienced and reflected on a traditional outdoor game for 12 weeks [35]. The other program engaged students in exploring topics related to local ecosystems, such as watershed and solar energy, for an academic year [34]. Both programs happened every year and incorporated technologies to support students' learning.…”
Section: Programs Involving Both Formal and Informal Contextsmentioning
confidence: 99%
See 3 more Smart Citations